Use and Regulation of Cannabis: A Global Debate on Medical and Recreational Cannabis (REMUNOM, 2023)
The use and regulation of cannabis have been a subject of discussion in many parts of the world. The lack of regulation for both recreational and medicinal purposes sparks debates about legal costs, public interest, and the need for regulation for cannabis-derived medications. In Brazil, the situation is complicated as marijuana possession is considered a crime, while harmful substances like Paraguayan cigarettes are allowed. The research emphasizes the importance of regulating the cultivation, extraction, and sale of pharmaceutical-grade substances as it can boost the economy and reduce costs of cannabis-related medications. It also highlights the potential benefits of cannabis, both medicinally and economically, and the need to address cultural and social prejudices.